Assessment of Physicochemical Properties of the Ovwian Section of the Warri River - Anderson , Faith Ekene; Duke, Okoro (International Journal of Scientific Research and Management (IJSRM), 2023)
This study evaluates the physical, chemical and heavy metal properties of the Ovwian Section of Udu River, Delta State, Nigeria with a view of ascertaining the water quality and establishing the correlation with national and international standards and activities around the water body. The physicochemical properties analyzed include pH, temperature, dissolved oxygen, total solids, total suspended solids, biological oxygen demand, salinity, alkalinity, total hardness amongst others. Some of the heavy metals studied include copper, chromium, iron, zinc, manganese and lead. The mean temperature (25.92±0.50oC), total dissolved solid (mean concentration - 22.53±5.46 mg/L), electrical conductivity (35.27±8.60 µS/cm), dissolved oxygen (mean concentration of 7.23±0.31 mg/L), biological oxygen demand (mean concentration - 2.01±0.84 mg/L), total hardness, nitrates (mean concentration - 1.06±0.52 mg/L), sulphate (mean sulphate concentration - 13.90±0.86 mg/L) and total alkalinity (8.00 mg/L - 12.00 mg/L) values were found to be within the permissible limits of WHO and FEPA. On the other hand, the total suspended solid (7.09 mg/L), turbidity (mean concentration - 34.54±14.18 NTU), pH and total coliforms were above the permissible limits of the regulatory agencies used in the study. Among the heavy metals present, Lead showed a very high concentration above the tolerance limit of WHO and FEPA. The result shows that some level of pollution is associated with the Ovwian section of the Udu River and adequate treatment is thus recommended before it can be used for any purpose.